Effectiveness Analysis Of Employee Recruitment In Islamic Philanthropic Institutions - Rozikan, Rozikan; Fadhila, Anisa (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
The background of this research is that the Yogyakarta City Baznas is one of the best city-level Baznas, especially in terms of quality management. This is evidenced by the achievements made by Baznas in Yogyakarta. Indirectly, this proves that Baznas RI, including Baznas Yogyakarta, is professional and transparent, free from KKN practices and negative public perceptions when recruiting their employees. This study aims to determine how Baznas Yogyakarta City's recruitment process produces quality human resources to become input and reference for other Islamic Philanthropic Institutions. This research belonged to qualitative research, while the data collection was through interviews, observation, and documentation study. Besides, interviews were conducted with four informants: the Deputy Head of Field IV, Senior Executive Staff, Junior Executive Staff, and the Internal Audit Unit. The validity test of the data was done by using source and technique triangulation. The results of the study prove that the Yogyakarta City Baznas has carried out detailed recruitment methods in the recruitment process for prospective new employees. Baznas Kota Yogyakarta prioritizes internal methods through apprenticeship experiences and volunteering. Baznas Kota Yogyakarta, in selecting the right candidate, has special competencies for prospective employees. This is to create quality human resources and support the success of the institution. So it is proven that the achievements that have been produced are in accordance with the recruitment process to produce quality employees.